The Dead Sea Scrolls and Variant Readings in Jerome's Psalterium iuxta Hebraeos: The Fourth Book of the Psalter (Psalms 90–106) as a Case Study = Die Schriftrollen vom Toten Meer und abweichende Lesarten im Psalterium iuxta Hebraeos des Hieronymus : das vierte Buch des Psalters (Psalmen 90-106) als Fallstudie - Jaspers, Martijn (Vulgata in dialogue, 2022)
This paper examines the textual variants in the fourth book of the Psalter (Psalms90–106) found in the Dead Sea Scrolls and compares these readings with Jerome’s Psalteriumiuxta Hebraeos. Even though these variants are not exhaustively listed in current editions ofthe Hebrew and Latin editions of the Psalms, several interesting agreements between readingsin the Dead Sea Scrolls and Jerome’s Psalterium iuxta Hebraeos can be found.